DEVELOPMENT OF E-MODULES BASED ON PROJECT BASED LEARNING (PjBL) TO INCREASE STUDENTâ€™S INTEREST IN LEARNING AND LEARNING OUTCOMES ON REACTION RATE MATERIAL - Siregar, Nurhidayah; Syafriani, Dewi (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2024)
This research aims to: (1) determine the validity of e-modules based on project based learning, (2) determine the practicality of e-modules based on project based learning, (3) determine the effectiveness of e-modules based on project based learning, and (4) determine whether there is a significant correlation between interest and learning outcomes. This research was conducted at SMA Negeri 10 Medan with the sample studied was class XI IPA 2. The data analysis technique is carried out by: e-module feasibility test according to BSNP, learning interest test, and correlation test between learning interest and learning outcomes. The results obtained in this research are: (1) E-modules based on project based learning are considered "valid" after being validated by 1 chemistry lecturer with an average material assessment of 89% and an average media assessment of 92% which can be categorized as â€œvery feasibleâ€; (2) e-modules based on project based learning can be considered "practical" after receiving chemistry teacher responses with an average percentage of 94% which can be categorized as "very feasible" and student responses with a grade of "very feasible". average grade of 98%; (3) e-module based on project based learning is considered "effective" with a posttest score of 93, an increase from 58, resulting in an N-Gain score of 0.83 (83%), which means it is in the high criteria; (4) There is a positive and significant relationship between interest in learning and student learning outcomes where â€œrhitungâ€ is 0.6471 and â€œrtabelâ€ is 0.361. Article HistoryÂ Â Â Â Â